(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
The study was conducted in Lattakia Governorate in 2022, with the aim of studying the impact of place of residence and income of consumer on broiler chicken consumption, and studying the market and consumer situation in light of high prices. The study population consists of all families in Lattakia Governorate, while the study sample was randomly selected from families in different regions of Lattakia Governorate. A questionnaire was developed for the objectives of the study, benefited of the theoretical study. The data was analyzed using the most important statistical methods, and the descriptive, analytical approach and tools of econometric were used to achieve the objectives of the study. The results of the study showed that there is a correlation between the place of residence of consumer and his consumption of broiler chicken meat, as the difference in the place of residence of the consumer leads to a difference in the consumption of broiler chicken meat by households، and a correlation was found between the consumption of broiler chicken meat and consumer’s income. As consumption depends mainly and directly on income، and changes in income affect the rate of consumption، increasing income leads to improving consumption